2022
DOI: 10.1155/2022/5263021
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention of Dexmedetomidine on Postoperative Delirium and Early Postoperative Cognitive Dysfunction in Elderly Patients Undergoing Thoracoscopic Lobectomy

Abstract: Objective. To investigate the effect of dexmedetomidine on postoperative cognitive function and delirium in elderly patients undergoing thoracoscopic lobectomy. Methods. 109 elderly patients (age is more than 65 years) who underwent thoracoscopic lobectomy in our hospital from June 2020 to Feb 2022 were randomly divided into the dexmedetomidine (DEX) group (n = 54) and the control group (n = 55). The patients in the experimental group were given dexmedetomidine by intravenous pump, intravenous pump 0.5 μg/kg w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…A total of 48 articles were included in this study (Table 1), of which 39 (81.25%) studies were cohort, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][39][40][41][42][45][46][47][49][50][51]54,57,[59][60][61][62][63][64][65][66][67][68] and 8 (16.6%) were randomized clinical 38,43,44,48,52,53,55,58 trials (one article excluded in the late stage as it was retracted in the publisher journal).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 48 articles were included in this study (Table 1), of which 39 (81.25%) studies were cohort, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][39][40][41][42][45][46][47][49][50][51]54,57,[59][60][61][62][63][64][65][66][67][68] and 8 (16.6%) were randomized clinical 38,43,44,48,52,53,55,58 trials (one article excluded in the late stage as it was retracted in the publisher journal).…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is the most promising pharmacologic agent in reducing the incidence of POD in the elderly, critically ill, and ventilated patients 22 , 49 , 50 . Two new prospective studies revealed that dexmedetomidine infusions were associated with a decreased incidence of POD in thoracoscopic lobectomy and coronary artery bypass procedures 21 , 51 . It is nevertheless premature to suggest that dexmedetomidine may reduce POD.…”
Section: Intraoperativementioning
confidence: 99%
“…Various factors can trigger postoperative cognitive impairment in patients, such as age, low educational level, high-risk surgical types, postoperative complications, postoperative infections, and others; its occurrence may also be related to central nervous system in ammation, neurotransmitter abnormalities and others [3]. Researches have shown that dexmedetomidine (Dex) can effectively reduce the incidence of POCD after cardiac [4] and non-cardiac surgeries [5][6][7][8]. However, no studies has examined how different Dex doses affect POCD in elderly female patients after LC.…”
Section: Introductionmentioning
confidence: 99%